Detecting the Corrosion of a Steel Rebar Using the Eddy Current Testing Method - Dongfeng He (Standards)
The corrosion of the steel reinforcing bar (rebar) reduces the strength capacity of concrete structures. Corrosion detection at the early stage of steel rebar implementation is important for the maintenance of concrete structures. Using the eddy current testing method, we developed a portable system to evaluate the corrosion of steel rebars. An AC current was sent to the excitation coil to produce an AC magnetic field and an eddy current was induced in the steel rebar. A detection coil was used to detect the signal produced by the eddy current. A lock-in amplifier was used to obtain the same phase signal and a 90-degree phase difference signal and an X-Y graph was plotted. From the slope of the X-Y graph, the corrosion of the steel rebar or steel wire can be evaluated. We examined the effects of excitation frequency, coil type, and coil size on the experimental results to optimize the system. The signal-to-noise ratio and the detection depth were improved with a specially designed probe.